From mine to user : production and procurement systems of Siliceous rocks in the European Neolithic and Bronze Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) - Bostyn, Françoise,; Giligny, François,; Topping, Peter, (UISPP proceedings series ;, 2021)
This title presents papers from parts 1 and 2 of session XXXIII of the 18th UISPP World Congress (Paris, June 2018). The first part, 'Siliceous rocks: procurement and distribution systems', looks at production systems and the diffusion of mining products, while the second, 'Flint mines and chipping floors', focuses on knapping activities.